Wegener's granulomatosis mimicking like pulmonary tuberculosis and presenting as cavitating lung disease with mycetoma: A case report with review of literature - Shital Patil; Deepak Patil (Wolters Kluwer Medknow Publications, 2022)
Pulmonary tuberculosis (TB) is the most common cause of bilateral pulmonary cavities with constitutional symptoms in India being endemic and more prevalent nature of the disease, irrespective of microscopy or nucleic acid amplification test abnormalities. Pulmonary manifestations of systemic vasculitis have very diverse involvement ranging from nodule, consolidation, and cavitation. In this case report, a 45-year-old female, presented with constitutional symptoms with lung parenchymal consolidations progressed to cavitation, and started empirical anti-TB treatment without mycobacterial microscopic or genome documentation in sputum with clinical or radiological worsening. Bronchoscopy workup is inconclusive and the tropical screen for bacterial, TB, and malignancy was negative and fungal yield Aspergillus colonization. A vasculitis workup was done in the presence of clinical and radiological worsening documented PR3-antineutrophil cytoplasmic antibody positive with very highly raised titers. We have started on steroids and cyclophosphamide with antifungals and clinical response was documented with a near-complete resolution of shadows in 24 weeks.